Pengaruh Pemberian Lapisan Lilin Pada Benih Tanaman Karet Selama Masa Simpan Terhadap Daya Kecambahnya - Pujiono, Saputra; Yulistriani, Yulistriani (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2022)
Rubber plants are an important plantation commodity as a source of non-oil and gas foreign exchange for Indonesia so they have a bright future. Propagation of rubber plants by grafting depends on the quality of the rootstock, and the graft as well as the grafter. The rootstock for rubber seedlings comes from seeds classified as recalcitrant. They have high moisture content, short shelf life, quickly loose their ability to germinate, and their cells freeze if stored at temperatures below 0oC. This study aimed to extend the shelf life of rubber seeds using a wax coating technique. The study was carried out for 2 months at the Unand campus III laboratory. A completely randomized divided plot design consisting of two factors, namely application of wax layer and shelf life was used. Application of wax slowed rubber seed germination. Various explanations are possible for this observation. One is that the ratio of wax/water in the suspension used to apply the wax layer was not appropriate. The longer the seeds were stored the lower the percentage germination observed. Therefore, further research should be conducted using less than 50% wax in the suspension use to coat the seeds.